A New Species of Austrelmis Brown from Argentina (Insecta: Coleoptera: Elmidae) - Martínez Román, Nicolás Rafael (2017)
A new species of Austrelmis, A. uaik sp. nov., from Patagonia, is described from adults of both sexes. Mature larvae of this species are also described and illustrated in detail. Adults of A. uaik are compared with those of A. patagonica, the only other species known from Patagonia and with other described argentine Austrelmis species. Larvae of A. uaik are compared to other previously described larvae from Argentina. A key to the known species of Austrelmis known from Argentina is included.